Ochrona praw człowieka we współczesnym Liechtensteinie. Zarys problematyki - Koźbiał, Krzysztof (Polityka i Społeczeństwo, 2020)
Liechtenstein is undoubtedly one of the countries where respect for human rights is at a high level. The reasons for this should be sought first of all in the decision of this micro-state to join the most important international organizations emphasizing the protection of human rights (UN, Council of Europe) as well as internal regulations that are of an increasingly higher standard. This does not mean that there are no problems or puzzling situations for researchers of the political affairs in this country in this respect. These include undoubtedly the relatively late granting of political rights to women and the actual lack of political rights of persons without the citizenship of the Principality, accounting for 1/3 of the country’s population.